2017
DOI: 10.1080/10401334.2017.1365719
|View full text |Cite
|
Sign up to set email alerts
|

High-Stakes Collaborative Testing: Why Not?

Abstract: Students described a range of heightened emotions around the collaborative test yet perceived it as valuable regardless if they were in established or newly formed teams. Students described learning about the subject matter, themselves, others, and interpersonal dynamics during collaborative testing. Triangulation of these results via quantitative data supported these themes. Insights: Despite student concerns, high-stakes collaborative tests may be both valuable and feasible. The data suggest that high-stakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In higher education, students are exposed to high levels of stress and anxiety revolving around their performance in assessments, such as quizzes, reports, and exams (Kapitanoff 2009, Dahlström 2012, Cantwell et al 2017, Johanns et al 2017, Levine et al 2017, Khansari and Coyne 2018. In this research, we apply gamification on the course element of assessment activities with a reward structure that connects them toward midterm and final exams to explore its effects on students' content knowledge and perceptions on satisfaction, experience, learning, and impact of teaching methods.…”
Section: Design Elements and The Course Choicementioning
confidence: 99%
“…In higher education, students are exposed to high levels of stress and anxiety revolving around their performance in assessments, such as quizzes, reports, and exams (Kapitanoff 2009, Dahlström 2012, Cantwell et al 2017, Johanns et al 2017, Levine et al 2017, Khansari and Coyne 2018. In this research, we apply gamification on the course element of assessment activities with a reward structure that connects them toward midterm and final exams to explore its effects on students' content knowledge and perceptions on satisfaction, experience, learning, and impact of teaching methods.…”
Section: Design Elements and The Course Choicementioning
confidence: 99%
“…47 Other studies have focused on the broad positive experience for the individual, such as in a medical education psychiatry test where students learnt both about the subject matter and themselves through the interpersonal dynamics of the situation. 53 Other studies showed the clear advantage even for the strong students in the class, 38,54 but effect on stress and anxiety seem to have somewhat mixed outcomes. 54,55 Students also proposed suggestions to improve the two-stage examination.…”
Section: Discussionmentioning
confidence: 98%
“…Two‐stage examinations proved effective in geology, 51 in accounting, 52 and were shown to reduce the achievement gap in oceanography 47 . Other studies have focused on the broad positive experience for the individual, such as in a medical education psychiatry test where students learnt both about the subject matter and themselves through the interpersonal dynamics of the situation 53 . Other studies showed the clear advantage even for the strong students in the class, 38,54 but effect on stress and anxiety seem to have somewhat mixed outcomes 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…We posit that this learning curve may not have been as remarkable had there not been the extrinsic motivation of an assessment - supported by comments like, “time pressure means we’re all willing to communicate effectively, so has greatly increase[d] this skill” (Additional file 2 ). Thirdly, collaborative testing may result in learning about oneself, others and interpersonal dynamics [ 34 ]. Many of the students’ comments around CSI improving understanding of others’ perspectives are relevant not only to patients but to team-members.…”
Section: Discussionmentioning
confidence: 99%